Johann Gottlob von Quandt (1787−1859) Kunst fördern und ausstellen - Rüfenacht, Andreas (De Gruyter, 2019)
Quandt was the builder of a first Goethe memorial site, founder of the Saxon Kunstverein and pioneer for a modern art gallery in Dresden. He promoted contemporary artists and explored Old Masters. He wanted his fellow citizens to be educated by art and tirelessly contributed to it with talks, articles and exhibitions. This study highlights the bustling personality and its work in the early 19th century. Quandt's broad commitment left deep traces in German cultural life and gave the young art history significant impulses. Therefore it is worth taking a look at his biography, his written legacies, his private collection with works of such well-known names as Overbeck, Schnorr von Carolsfeld, Friedrich, Botticelli, Fra Angelico and Cranach.